From bioeconomics to bioeconopysis in the context of (bio)diversity and modern morality - Yuichi Tei; Gheorghe Săvoiu (Amfiteatru Economic Journal, 2018)
The article develops a complex interdisciplinary paradigm, or rather a multiparadigm of bioeconomics, exemplifying the necessary role and the broader horizon of multidisciplinarity through bioeconophysics, in the context of (bio)diversity and modern morality, in a logically investigative and coherently summarized approach. A brief conceptual introduction is followed by the first section, dedicated to identifying the actual approach, going from scientific unidisciplinarity to modern multidisciplinarity, selecting and validating, out of the three hypotheses of plausible paths towards bioeconomics (BioEconoPhysics), Biophysical Economics or EconoBioPhysics, the one appropriately supported by arguments and historically motivated, but also because of the clarity of the methods and the consistency of the specific models. A second important section of the paper outlines the current context of (bio)diversity and morality, which is specific to bioeconomics, biophysics or econophysics, as well as the result of their interstitial or multidisciplinary unification, proving the usefulness of some detailed characteristic modern tendencies, relating to the opinions of, and relationships of science with ethics. Some final remarks and perspectives of econobiophysics or bioeconomics symmetrically close the outline of the article.
Keywords: A12; B29; N01; Q57; I23; Y80; 330; bioeconomics; bioeconomy; biophysics; econophysics; bioeconophysics; economic biophysics; econobiophysics; economics; thermodynamics; (bio)diversity; morality; inter- and multidisciplinarity